Capparis danielii (Capparaceae), a new species from the Gulf of Mannar Biosphere Reserve, India - Murugan, C.; Manikandan, R.; Nithya, S.p.; Karthik, B.; Arisdason, W. (Phytotaxa, 2020)
A new species, Capparis danielii (Capparaceae), is described from the Gulf of Mannar Biosphere Reserve, Tamil Nadu, India. This new species was found in the coastal dry evergreen scrubs, and only three individuals were recorded from the type locality. It is very closely allied to C. brevispina and C. divaricata but can easily be distinguished from them by its glaucous branchlets, ovate-obovate leaves, short gynophore, oblong, 4-angular, pubescent ovary and usually longitudinally 4-ribbed, or rarely 6-ribbed berry. Detailed description, illustration, colour photographs, flowering and fruiting period and habitat ecology of the new species are provided.